(untitled) (Indonesian Journal of Civil Engineering Study, 2025)
Planning for Wedung Road as an alternative route from Mijen Demak to Demak City, the Mijen District Route, Demak Regency is a route that connects Demak Regency to Jepara Regency. The Mijen Demak route has 2 undivided lanes, each lane is approximately 3 meters wide. This traffic diversion causes the Mijen road in Demak Regency to become congested due to limited lane width so that queues often occur. Therefore, to reduce the queue of vehicles on Jalan Wedung, it is necessary to widen the road. The aim of this research is to plan the rigid pavement of Jalan Wedung, Mijen District, Demak using the 2017 Bina Marga Method and geometric planning of Jalan Wedung, Mijen District, Demak. The preparation stages carried out include literature studies regarding all rigid pavement planning materials. Determine all necessary data requirements. The f’s 45 concrete surface layer is 26.5 cm thick, the thin concrete/LMC f’c10 MPa layer is 10 cm thick, the class A aggregate foundation layer is 15 cm thick and the selected embankment is 3 m thick. Using dowel diameter 32 mm, distance 300 mm, length 45 cm. using tie bars with a diameter of 16 mm, a distance of 850 mm and a length of 65 cm. In this study, the CBR test value for Mijen soil was used. The results of the CBR test data distribution show a CBR value of 12.82%. The geometric planning of Jalan Wedung shows a concave type vertical alignment with a vertical curve length of L = 48 m and a horizontal alignment with a total of 3 bends, with a spiral - spiral type.